Morphometric Changes in Patients with Chronic Kidney Disease who Died Related to Diabetes Mellitus, Arterial Hypertension and Obesity - Ivette Gómez Fernández; Adys Castro Barberena; Greta Margarita Arrechea García; Georgina Jiménez Estrada; Javier Martínez Navarro; Domingo Fuentes Febles (Revista Finlay)
Background: chronic kidney disease has increased its incidence, there are no studies in Cuba or in the province on renal morphometry in patients with chronic kidney disease who have undergone autopsy. Objective: to determine renal morphometric variations in deceased patients who have undergone autopsy at the Dr. Gustavo Aldereguía Lima University General Hospital of Cienfuegos. Method: a descriptive, longitudinal and retrospective study was carried out. The universe was made up of 85 deceased patients who underwent autopsy with a clinical diagnosis of chronic kidney disease at any stage. We worked with the whole universe. The variables studied were: age, sex, weight and height for the calculation of the body mass index, personal pathological history, the clinical stage of chronic kidney disease and renal morphometry to each organ separately, the measurements made were: weight, longitudinal diameter, transverse diameter, thickness or thickness of the renal cortex. The data was processed in the statistical package of SSPS v. 11.5 presenting tables in absolute numbers and percentages. Results: the female sex predominated, aged between 70-79 years, with clinical stage I and IV of chronic kidney disease, the obese represented 57.6 %, the hypertensive 67.1 % and the diabetic 25.8 %. There was a decrease in all morphometric variables in both kidneys, highlighting the thickness of the renal cortex. Conclusions: there was a relationship between hypertension, diabetes mellitus and obesity with renal morphometric variables.